Irritant Inhalation Evokes P Wave Morphological Changes in Spontaneously Hypertensive Rats via Reflex Modulation of the Autonomic Nervous System - Hooper, J. Shane; Taylor-Clark, Thomas E. (Frontiers in Physiology, 2021)
Irritant inhalation is associated with increased incidence of atrial fibrillation (AF) and stroke. Irritant inhalation acutely regulates cardiac function via autonomic reflexes. Increases in parasympathetic and sympathetic reflexes may increase atrial susceptibility to ectopic activity and the initiation of arrhythmia such as AF. Both age and hypertension are risk factors for AF. We have shown that irritant-evoked pulmonary-cardiac reflexes are remodeled in spontaneously hypertensive (SH) rats to include a sympathetic component in addition to the parasympathetic reflex observed in normotensive Wistar-Kyoto (WKY) rats. Here, we analyzed P wave morphology in 15-week old WKY and SH rats during inhalation of the TRPA1 agonist allyl isothiocyanate (AITC). P wave morphology was normal during vehicle inhalation but was variably modulated by AITC. AITC increased RR intervals (RRi), PR intervals and the P wave duration. In SH rats only, AITC inhalation increased the occurrence of negative P waves. The incidence of AITC-evoked negative P waves in SH rats was dependent on RRi, increasing during bradycardic and tachycardic cardiac cycles. Inhibition of both parasympathetic (using atropine) and sympathetic (using atenolol) components of the pulmonary-cardiac reflex decreased the incidence of negative P waves. Lastly, the probability of evoking a negative P wave was increased by the occurrence of preceding negative P waves. We conclude that the remodeled irritant-evoked pulmonary-cardiac reflex in SH rats provides a substrate for altered P wave morphologies. These are likely ectopic atrial beats that could provide a trigger for AF initiation in structurally remodeled atria.